MLA handbook for writers of research papers / Joseph Gibaldi, Walter S. Achtert - Joseph, Gibaldi
For nearly half a century, the style recommended by the Modern Language Association of American for schoolarly manuscripts and student research papers has been widely adopted not only by journals and university presses but also bu graduate school, college departments, and individual instructors. The MLA handbook for writers of research papers, incorporating MLA style guidelines, serves as a suplementary text in writing courses or as a reference book for students to use independently.